Utilization of Instagram as a Promotional Means to Increase Sales at Kaliraya Mushroom MSMEs, Menang - Fergianto, Febrian Angga (Proceeding Kilisuci International Conference on Economic & Business, 2024)
R Research aim: This research aims to determine the benefits of Instagram as a promotional means to increase sales at mushroom MSMEs in Kaliraya, Menang. Design/Methode/Approach: This research uses a qualitative method, with data collection techniques such as interviews, observation, and documentation. The object of this research is Kaliraya Mushroom MSMEs, Menang. Research Finding: The research results show that using Instagram as a promotional means increases sales. Theoretical contribution/Originality:- Practitioner/Policy implication:- Research limitation: There is a lack of in-depth observation, so this research may not be able to explore details of effective promotional strategies or detail the experiences of Kaliraya Mushroom MSMEs in overcoming certain obstacles on Instagram.